A breeding strategy to identify modifiers of high genetic risk for methamphetamine intake. (17th June 2020) - Reed, Cheryl; Stafford, Alexandra M.; Mootz, John R. K.; Baba, Harue; Erk, Jason; Phillips, Tamara J.
Abstract: Trace amine‐associated receptor 1 ( Taar1 ) impacts methamphetamine (MA) intake. A mutant allele ( Taar1 m1J ) derived from the DBA/2J mouse strain codes for a non‐functional receptor, and Taar1 m1J/m1J mice consume more MA than mice possessing the reference Taar1 + allele. To study the impact of this mutation in a genetically diverse population, heterogeneous stock‐collaborative cross (HS‐CC) mice, the product of an eight‐way cross of standard and wild‐derived strains, were tested for MA intake. HS‐CC had low MA intake, so an HS‐CC by DBA/2J strain F2 intercross was created to transfer the mutant allele onto the diverse background, and used for selective breeding. To study residual variation in MA intake existing in Taar1 m1J/m1J mice, selective breeding for higher (MAH) vs lower (MAL) MA intake was initiated from Taar1 m1J/m1J F2 individuals; a control line of Taar1 +/+ individuals (MAC) was retained. The lines were also examined for MA‐induced locomotor and thermal responses, and fluid and tastant consumption. Taar1 m1J/m1J F2 mice consumed significantly more MA than Taar1 +/+ F2 mice. Response to selection was significant by generation 2 and there were corresponding differences in fluid consumed. Fluid consumption was not different in non‐MA drinking studies. Taar1 m1J/m1J genotype (MAL or MAH vs MAC mice) was associated with heighted MA locomotor and reduced hypothermic responses. MAL mice exhibited greater sensitization than MAH mice, but the selected lines did not consistently differ for thermal or tastant phenotypes. Residual variation among high‐risk Taar1 m1J/m1J mice appears to involve mechanisms associated with neuroadaptation to MA, but not sensitivity to hypothermic effects of MA. Abstract : There was a significant bidirectional response to selection for methamphetamine consumption in Taar1 m1J/m1J animals.